2018
DOI: 10.1186/s13148-018-0541-9
|View full text |Cite
|
Sign up to set email alerts
|

Epigenome-wide DNA methylation regulates cardinal pathological features of psoriasis

Abstract: BackgroundPsoriasis is a chronic inflammatory autoimmune skin disorder. Several studies suggested psoriasis to be a complex multifactorial disease, but the exact triggering factor is yet to be determined. Evidences suggest that in addition to genetic factors, epigenetic reprogramming is also involved in psoriasis development. Major histopathological features, like increased proliferation and abnormal differentiation of keratinocytes, and immune cell infiltrations are characteristic marks of psoriatic skin lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 56 publications
2
65
0
Order By: Relevance
“…Thus, loss of 5-hmC in psoriasis appears to function, at least in part, in modulating gene expression important for maintenance of stem cell behavior during psoriasis pathogenesis. DNA methylation profiling in psoriasis has indicated previously that hypermethylation in lesional skin with altered expression of differentially methylated genes contributes to the psoriatic phenotype (Chandra et al, 2018;Zhang et al, 2010;Zhou et al, 2016). Successful treatment of psoriasis with phototherapy not only significantly reduced the histopathological features in psoriasis, but also reverted DNA methylation to a more normal pattern (Gu et al, 2015;Ozkanli et al, 2015).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, loss of 5-hmC in psoriasis appears to function, at least in part, in modulating gene expression important for maintenance of stem cell behavior during psoriasis pathogenesis. DNA methylation profiling in psoriasis has indicated previously that hypermethylation in lesional skin with altered expression of differentially methylated genes contributes to the psoriatic phenotype (Chandra et al, 2018;Zhang et al, 2010;Zhou et al, 2016). Successful treatment of psoriasis with phototherapy not only significantly reduced the histopathological features in psoriasis, but also reverted DNA methylation to a more normal pattern (Gu et al, 2015;Ozkanli et al, 2015).…”
Section: Discussionmentioning
confidence: 97%
“…DNA methyltransferases are known to be essential in preserving the self-renewing capacity of stem cells by maintaining DNA methylation patterns (Sen et al, 2010). Genome-wide studies have established aberrant DNA methylation sites that correlate altered gene expression with major histopathological features of psoriasis (Chandra et al, 2018;Zhou et al, 2016). Furthermore, restoration to a more normal methylation status at specific loci was seen in patients who experienced improvement of their psoriasis from antietumor necrosis factor a therapy or UVB phototherapy (Gu et al, 2015;Roberson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies by Chandra et al and Zhao et al report epigenome-wide DNA methylation as one of the features playing a key role in psoriasis [21,29]. The study by Chandra revealed a significant difference in the enrichment of methylated CpGs in PSORS regions, where it shows an inverse correlation with higher gene expression [29]. A link between histopathological findings (such as Munro's microabscess, parakeratosis, and neutrophil accumulation) has also been established [29].…”
Section: State Of Knowledgementioning
confidence: 99%
“…The study by Chandra revealed a significant difference in the enrichment of methylated CpGs in PSORS regions, where it shows an inverse correlation with higher gene expression [29]. A link between histopathological findings (such as Munro's microabscess, parakeratosis, and neutrophil accumulation) has also been established [29]. Zhao reports that global DNA methylation is significantly increased in peripheral blood mononuclear cells and skin lesions of psoriatic patients compared to healthy controls [21].…”
Section: State Of Knowledgementioning
confidence: 99%
“…One of the most characteristic symptoms of this disease is the phenomenon of parakeratosis, that is, the keratosis of the epidermis being accelerated by about eight times the regular speed (Albanesi, ; Reali & Brembilla, ). The role and contribution of genetic, environmental, and epigenetic factors in the context of induction and development of psoriasis is widely discussed and analyzed (Chandra, Senapati, Roy, Chatterjee, & Chatterjee, ; Kimmel & Lebwohl, ). It seems that a key factor in understanding the nature of the inflammation underlying this disease is the assessment of changes at the molecular level (Hacker, Hoermann, & Kenner, ; Salto‐Tellez, ; Zhao et al, ).…”
Section: Introductionmentioning
confidence: 99%